A terapia comunitária enquanto instrumento para a construção de práticas de cuidado: uma abordagem a partir das redes sociais - Breno Augusto Souto Maior Fontes (Ciências Sociais Unisinos)
This article aims to present some practices for people with mental health problems. These practices are anchored in social support developed through the hearing and discussing the stress factors (mainly resulting from the lack of adequate social condition of life) that contribute to recover from these mental disorders. During the direct observation of the so-called Communitarian Therapy in the Neighborhoods of Engenho do Meio and Brasilit in Recife, Federal State of Pernambuco I had the opportunity to examine how these practices trigger social support between the participants, promoting thus important forms of resilience to cope with suffering. The methodology used employs qualitative methods, with direct observation, semi-structured interviews and also the construction of indicators of socio-centered networks of people participating in the Communitarian Therapy activities.